2006
DOI: 10.1211/jpp.58.5.0014
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological potential ofSorbus commixtacortex on blood alcohol concentration and hepatic lipid peroxidation in acute alcohol-treated rats

Abstract: The effect of Sorbus commixta cortex, a traditional herbal medicine used for the treatment of bronchitis, gastritis and dropsy, on blood alcohol concentration (BAC) and hepatic lipid peroxidation was examined in acute alcohol-treated rats. A 30-min pretreatment with a methanol extract of S. commixta cortex (SC) at concentrations higher than 200 mg kg(-1) resulted in a significant decrease in BAC and the ethyl acetate fraction (SE) of the extract showed the highest potency, with a maximum of a 46% decrease at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…Rowanberry fruits are used in the management of various diseases such as intestinal obstructions, chronic diarrhea, coronary heart diseases, different types of cancer (Fan and others ), long‐term diabetic complications (Termentzi and others ), liver, and gallbladder conditions and the prevention of inflammation (Yu and others ; Hong and others ). Additionally, through the protection of hepatic catalase, these fruits reduce hepatic lipid peroxidation by decreasing the bioavailability of alcohol and its oxidative metabolites (Lee and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Rowanberry fruits are used in the management of various diseases such as intestinal obstructions, chronic diarrhea, coronary heart diseases, different types of cancer (Fan and others ), long‐term diabetic complications (Termentzi and others ), liver, and gallbladder conditions and the prevention of inflammation (Yu and others ; Hong and others ). Additionally, through the protection of hepatic catalase, these fruits reduce hepatic lipid peroxidation by decreasing the bioavailability of alcohol and its oxidative metabolites (Lee and others ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, the flavanol glycosides, catechin-7-O--D-xylopyranoside and catechin-7-O--D-apiofuranoside, isolated from this species, were found to have antioxidant activity [9]. Recently, its extract was demonstrated to have beneficial effects on atherosclerosis and protective effect on hepatic lipid peroxidation in acute-alcohol treated model [10,11]. However, there has been no study with regard to its inhibitory effect on PTP1B.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol extracts of S. commixta bark have photoprotective effects [9]. Experiments with rats pretreated with methanol extracts of S. commixta cortex revealed antitoxic effects of the extracts [10]. It was found that methanol and butanol extracts of S. commixta cortex have vasodilating properties [11,12], while methanol extracts have antiatherogenic effects [13,14].…”
mentioning
confidence: 99%